Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

tan a + sin a = m & tan a - sin a = n prove that m2 - n2 4square root of m n end root

Asked by Vinay 6th April 2017, 1:47 PM
Answered by Expert
Answer:

Given that tan a + sin a = m and tan a - sin a = n 

Consider,

mn = (tan a + sin a) (tan a - sin a) 

mn = tan2 a - sin2 a =begin mathsize 12px style fraction numerator sin squared straight a over denominator space cos squared space straight a end fraction minus sin squared straight a end style

mn = begin mathsize 12px style sin squared space straight a open parentheses fraction numerator 1 over denominator space cos squared space straight a end fraction minus 1 close parentheses end style

mn = begin mathsize 12px style sin squared space straight a open parentheses fraction numerator 1 minus space cos squared space straight a over denominator space cos squared space straight a end fraction close parentheses end style  

mn = tan2 a  × sin2 a      .......( i ) 

Consider,

LHS = m2 - n2

        = (tan a + sin a )2 - (tan a - sin a)2 

        = tan2 a  + sin2 a   + 2 tan A sin A - tan2 a   - sin2 a  + 2 tan A sin A 

        = 4 tan A sin A 

        = 4square root of mn [from equation ( i )] 
        = RHS

Hence proved.

If you have any other query, do attend the FREE webinar (Online Class) on 12th April from 4 pm to 5 pm.

Answered by Expert 6th April 2017, 2:11 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!